(untitled) (Research, Society and Development, 2021)
Recently, the academic world has been discussing the theory called “cross-kingdom transfer” in the nutritional scope. It has the idea that bioactive genetic material has the potential to be transferred from plants to animals via the gastrointestinal tract. Upon reaching its site of action, this exogenous molecule would be able to influence the pathophysiological conditions of its recipient organism. MicroRNAs (miR) are molecules listed as capable of carrying out this action. They are responsible for adhering to messenger RNA molecules and preventing their translation, thereby regulating various cellular mechanisms, including cell cycle control. This review article aimed to provide an overview of research in this controversial field. It is concluded that, although more research is needed in order to clarify issues related to the theme, some studies indicate that food can serve to the transfer of miRNAs from one kingdom or from one species to another.